2008
DOI: 10.1182/blood-2007-02-075945
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib, but not sunitinib, affects function of dendritic cells and induction of primary immune responses

Abstract: IntroductionMetastatic renal cell cancer (RCC) has a very poor prognosis with a median survival of only 6 to 12 months from the time of diagnosis. 1,2 Historically, there were no established effective treatment approaches for metastatic RCC because of its resistance to radiation and chemotherapy. 3 Until recently, cytokine-based immunotherapy using interferon-␣ (IFN-␣) and/or interleukin-2 (IL-2) was the only effective treatment resulting in response rates of 10% to 20%. 4 The understanding of RCC pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
234
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(253 citation statements)
references
References 59 publications
15
234
1
3
Order By: Relevance
“…The role of VEGF in the expansion of Tregs within the tumor microenvironment may explain the observation that some antiangiogenic molecules decrease the number of both circularing and intratumoral Tregs in cancer patients [73][74][75][76]. Intriguingly, although all these antiangiogenic molecules efficiently inhibit the VEGF/VEGFR axis, sunitinib appears to be more potent at decreasing the number of Tregs than many other agents including sorafenib, whose Tregmodulatory potential remains matter of debate [75,[77][78][79][80].…”
Section: Tregs and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The role of VEGF in the expansion of Tregs within the tumor microenvironment may explain the observation that some antiangiogenic molecules decrease the number of both circularing and intratumoral Tregs in cancer patients [73][74][75][76]. Intriguingly, although all these antiangiogenic molecules efficiently inhibit the VEGF/VEGFR axis, sunitinib appears to be more potent at decreasing the number of Tregs than many other agents including sorafenib, whose Tregmodulatory potential remains matter of debate [75,[77][78][79][80].…”
Section: Tregs and Angiogenesismentioning
confidence: 99%
“…Intriguingly, although all these antiangiogenic molecules efficiently inhibit the VEGF/VEGFR axis, sunitinib appears to be more potent at decreasing the number of Tregs than many other agents including sorafenib, whose Tregmodulatory potential remains matter of debate [75,[77][78][79][80]. Intriguingly, it has been shown that Tregs infiltrating breast carcinoma lesions are capable of promoting the metastatic dissemination of mammary carcinoma cells as they express on their surface the pro-metastatic TNF superfamily member RANKL [40].…”
Section: Tregs and Angiogenesismentioning
confidence: 99%
“…Sm is a broad-spectrum RTKI that targets VEGFR-1 and -2, CSF1-R, PDGFRα and β, cKIT receptor, and Flt-3 (36) and is approved for use in the treatment of renal cell cancer and imatinib-resistant or -intolerant GIST (37). As reversal of vascular remodeling is a suggested application of Sm (38), we used this drug to evaluate the effects of RTKIs on the development of splenomegaly and the outcome of infection.…”
Section: Splenomegaly In Experimental Vl Is Accompanied By Extensive mentioning
confidence: 99%
“…Anti-CTLA-4 antibodies will hopefully be approved soon [100], and can then be systematically tested also in the context of DC vaccines, which will be very interesting given promising observations in previously vaccinated patients [101,102]. Another possibility for ''off label'' use is Sunitinib, which appears to inhibit STAT3 [9], and could be combined with DC vaccination as it does not appear to block DC or antitumor T cells [103,104].…”
Section: Combination Therapiesmentioning
confidence: 99%